Methods for fully connecting IoT gadgets to LTE networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Connecting IoT devices to an architecture that allows for smooth transitions between services is becoming more important as the number of IoT-enabled devices in use grows. The number of internet-connected devices is expected to skyrocket from its current 10-billion strong to 34 billion by 2020.As time goes on, LTE systems become the ideal companion for meeting these evolving service needs. However, the signalling overhead in IoT systems will expand exponentially with the forthcoming expansion in the number of IoT devices. As a result, LTE systems' signalling overhead will rise. Due to the increasing number of exchanges between the transmitter and receiver, the current protocol stack of the LTE systems is not best adapted to manage the signalling traffic produced by the IoT devices. This suggested method not only boosts the speed of video flows but also improves the Quality of Service (QoS) of voice streaming via the Internet of Things. Even with the addition of IoT Traffic, numerical results demonstrated that the suggested strategy was able to boost overall system throughput. A crucial aspect of LTE-A systems is their ability to integrate seamlessly with other networks, which was made possible by the protocol stack and the scheduling mechanism.